2006
DOI: 10.2353/ajpath.2006.050868
|View full text |Cite
|
Sign up to set email alerts
|

Renewal of Mural Thrombus Releases Plasma Markers and Is Involved in Aortic Abdominal Aneurysm Evolution

Abstract: Human abdominal aortic aneurysm (AAA) expansion has been linked to the presence of a mural thrombus. Here we explored the mechanism of the continual luminal renewal of this thrombus and its ability to release biological markers potentially detectable in plasma. We also explored the ability of platelet inhibition to pacify the thrombus and to limit aneurysm progression in an experimental model. Blood samples and mural thrombi were collected in 20 AAA patients. In parallel, segments of sodium dodecyl sulfate-dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
159
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(177 citation statements)
references
References 58 publications
13
159
1
4
Order By: Relevance
“…As proposed by some authors 5 and shown in the present study, nonbacterial and bacterial thrombotic endocarditis share common pathological consequences, mainly linked to platelet procoagulant 22,32 and proteolytic activities conveyed by thrombus formation and degradation, 12 which are greatly amplified by biological activities conveyed by the bacteria themselves. 11,33 Therefore, whatever their predominant source, platelet proaggregant and procoagulant activities participate in the development of vegetations, fibrinolytic activities contribute to sepsis diffusion and embolic potential, and numerous proteases are involved in tissue destruction in relation to their ability to damage extracellular matrix and to induce cell death.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…As proposed by some authors 5 and shown in the present study, nonbacterial and bacterial thrombotic endocarditis share common pathological consequences, mainly linked to platelet procoagulant 22,32 and proteolytic activities conveyed by thrombus formation and degradation, 12 which are greatly amplified by biological activities conveyed by the bacteria themselves. 11,33 Therefore, whatever their predominant source, platelet proaggregant and procoagulant activities participate in the development of vegetations, fibrinolytic activities contribute to sepsis diffusion and embolic potential, and numerous proteases are involved in tissue destruction in relation to their ability to damage extracellular matrix and to induce cell death.…”
Section: Discussionmentioning
confidence: 73%
“…6,35 During activation, aggregation, and disintegration, platelets expose negatively charged phosphatidylserines, which are necessary for the assembly of tenase and prothrombinase complexes and thrombin generation, at the interface with circulating hemostatic blood components. 32,36 Therefore, platelet-exposed phosphatidylserine is the biological link between platelet activation and fibrin clot formation. Annexin V specifically binds with nanomolar affinity to phosphatidylserines.…”
Section: Discussionmentioning
confidence: 99%
“…Intraluminal thrombus is a consistent feature of AAA and usually has a laminar appearance with the mural component having been deposited first and subsequent growth of the thrombus occurring by further deposition of fibrin, platelets, and red blood cells on the inner luminal aspect. 29 The universal finding of a large change in T2* value in the periluminal region of the aneurysm is therefore likely to reflect trapping of USPIO in fresh potentially gelatinous thrombus that is typically friable and highly cellular because of its close proximity to flowing blood. 30 It was interesting to observe that this region also enhanced rapidly with gadolinium, consistent with a less selective and more generalized uptake of contrast agents in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that thrombosis is accompanied by degeneration of the aneurysm wall, as found in other experimental or human aortic aneurysms. [9][10][11][12] Inflammation of the venous wall was present in unruptured and in ruptured cases. In our model, the distinguishing factor was the presence of recanalization between the thrombus and the necrosing wall.…”
Section: Thrombosis Followed By Rupturesmentioning
confidence: 99%
“…7,8 Thrombusprecipitating rupture has also been implicated in abdominal aortic aneurysms. [9][10][11][12] However, because thrombosis followed by organization and neointimal closure of the neck is required for successful occlusion of aneurysms by endovascular embolization, 11,[13][14][15][16][17][18] there must be additional factors to account for thrombosis leading to rupture rather than occlusion. Such discriminating factors have not been explored experimentally, to our knowledge.…”
mentioning
confidence: 99%